Aktualne zagrożenia stabilności systemu finansowego w Polsce - Żukowski, Marian; Żukowska, Helena (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The stability of financial system is a major component of the economic securityof a state. An active role of state has a significant impact on ensuring the stabilityof financial system. The most important component of ensuring stability ofa financial system is to maintain stability of the banking sector. Stability of financialsystem is necessary for both the economy as a whole, individual sectors andall stakeholders, including individuals as it is a public good. Although the Polishfinancial system is now stable, three recent incidents need detailed examination:operations and the collapse of investment firm Amber Gold, instability on themortgage loans (denominated in Swiss Franc) market and the restructuring ofthe cooperative credit unions. From the financial point of view, the importance ofthese phenomena is marginal but from the public interest point of view it is vital.Therefore, there is a need to study "hybrid" dangers present in the framework ofthe financial system in Poland and to establish the Council on Systemic Risks aswell as to introduce new regulations to ensure safety of deposits. It is also necessaryto educate public about functioning of the financial market.